Cabozantinib Resolves Bone Scans in Tumor-Naïve Mice Harboring Skeletal Injuries - Michael G. Doran; Daniel E. Spratt; John Wongvipat; David Ulmert; Brett S. Carver; Charles L. Sawyers; Michael J. Evans (Molecular Imaging)
The receptor tyrosine kinase inhibitor cabozantinib (XL184, BMS-907351 Cometriq) has displayed impressive clinical activity against several indications, culminating in its recent approval for medullary thyroid cancer. Among malignancies with tropism for the bone (prostate, breast), one striking feature of early clinical reports about this drug has been the rapid and complete resolution of bone scans, a phenomenon almost never observed even among therapies already shown to confer survival benefit. In castration-resistant prostate cancer, not all conventional response indicators change as dramatically posttreatment, raising the possibility that cabozantinib may impair the ability of bone-seeking radionuclides to integrate within the remodeling bone. To test this hypothesis, we surgically induced bone remodeling via physical insult in non–tumor-bearing mice and performed 18 F-sodium fluoride ( 18 F-NaF) positron emission tomographic (PET) and technetium 99m–methylene diphosphonate ( 99m Tc-MDP) single-photon emission computed tomographic (SPECT) scans pre- and posttreatment with cabozantinib and related inhibitors. A consistent reduction in the accumulation of either radiotracer at the site of bone remodeling was observed in animals treated with cabozantinib. Given that cabozantinib is known to inhibit several receptor tyrosine kinases, we drugged animals with various permutations of more selective inhibitors to attempt to refine the molecular basis of bone scan resolution. Neither the vascular endothelial growth factor receptor (VEGFR) inhibitor axitinib, the MET inhibitor crizotinib, nor the combination was capable of inhibiting 18 F-NaF accumulation at known bioactive doses. In summary, although the mechanism by which cabozantinib suppresses radionuclide incorporation into foci undergoing bone remodeling remains unknown, that this phenomenon occurs in tumor-naïve models indicates that caution should be exercised in interpreting the clinical significance of this event.